KEBUTUHAN ENERGI PADA PEMBUATAN PAPAN PARTIKEL DARI TANDAN KOSONG KELAPA SAWIT, SERBUK KULIT PINUS DAN AKASIA - Sulaiman, Sulaiman; Tegar, Thomas (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2019)
Human needs for wood as building materials or furniture continue to increase along with the increase in population, while the availability of wood in the forest is both limited in number and quality. This affects the particle board industry which is increasingly difficult to get good quality solid wood. One alternative to replace wood particles is Oil Palm Empty Bunches which has enormous potential to be used in the engineering field, especially as raw material for making particle boards, by utilizing acacia bark as an adhesive (matrix). To make particle board energy is needed in the manufacturing process. The energy needed in the process of making particle boards is 47,446,211.61 Joules for 25 particle boards or for 1 board for 1,897,848.46 Joules. If converted to Rupiah, the value of one particle board is Rp. 5030. When compared with factory-made prices with a size of 120 cm x 250 cm with a thickness of 1.2 cm at a price of Rp. 90,000, the particle boards that have been made are more expensive than factory-made ones.